FALSAFAH PELA GANDONG DAN TOLERANSI BERAGAMA DALAM MASYARAKAT AMBON YANG MULTIKULTUR - A. Basir Solissa (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2014)
This article is an effort  to elaborate Ambonese Philosophy of Pela Gandong. The Society of Ambonese build up a wisdom called as Pela Gandong. It is a philosophy on how to bridge the differentiation between the peoples by its different in Religion and Culture. The Pela-Gandong cultural  system is a bond of friendship  and brotherhood expressed in familiar greetings such as Nyong Pee, Nona Pee, Gandongee, Bongsoee. It also covers activities of mutual cooperation in a better or worse  situation," This is a bond formed between individuals or villages, triggered by events of mutual assistance during a disaster, famine, or other adversities. The relationships formed are not based on family ties, and this helped people to live in harmony with the principle of mutual collaboration. The humanity dimension within these forms of bonding includes mutual assistance, tolerance, mutual trust, and brotherhood.